2013
DOI: 10.1093/ageing/aft207
|View full text |Cite
|
Sign up to set email alerts
|

UK medical teaching about ageing is improving but there is still work to be done: the Second National Survey of Undergraduate Teaching in Ageing and Geriatric Medicine

Abstract: Introduction: in 2008, a UK national survey of undergraduate teaching about ageing and geriatric medicine identified deficiencies, including failure to adequately teach about elder abuse, pressure ulcers and bio- and social gerontology. We repeated the survey in 2013 to consider whether the situation had improved.Method: the deans of all 31 UK medical schools were invited to nominate a respondent with an overview of their undergraduate curriculum. Nominees were invited by email and letter to complete an online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 12 publications
1
47
0
Order By: Relevance
“…It is important to highlight the limited time dedicated to geriatric medicine topics in undergraduate medical education and also its variability across Europe [10,14]; these findings add weight to the argument for the need for consensus on post-graduate training length, since the baseline competencies of new trainees is likely to be variable. There is also notable variety in the regulatory bodies that are responsible for post-graduate geriatric medicine training across European countries -these include national medical associations, health ministries and universities.…”
Section: Post-graduate Geriatric Medicine Training Across Europementioning
confidence: 99%
“…It is important to highlight the limited time dedicated to geriatric medicine topics in undergraduate medical education and also its variability across Europe [10,14]; these findings add weight to the argument for the need for consensus on post-graduate training length, since the baseline competencies of new trainees is likely to be variable. There is also notable variety in the regulatory bodies that are responsible for post-graduate geriatric medicine training across European countries -these include national medical associations, health ministries and universities.…”
Section: Post-graduate Geriatric Medicine Training Across Europementioning
confidence: 99%
“…National survey data from the United Kingdom in 2013 found the median time devoted to formal teaching about geriatric medicine was only 55 hours out of a five year programme [2].…”
Section: Introductionmentioning
confidence: 99%
“…These themes may in part be explained by the limited time allocated to specific teaching on geriatric medicine in UK medical schools. 7 As Gordon et al 7 stressed, simply being 'around' old people does not guarantee learning and understanding of core geriatric topics such as frailty, cognitive impairment or comprehensive geriatric assessment.…”
Section: Discussionmentioning
confidence: 99%
“…First, serial survey work has demonstrated that while there has been an increase in the number of UK medical schools teaching and assessing geriatric medicine, a comparatively small amount of time is allocated to teaching on ageing. 6,7 Second, evidence exists suggesting that some students have negative attitudes towards older people 8 and perceive the specialty to lack prestige. 9 Recent work by Ni Chroinin et al 10 examined the career preferences of a cohort of medical students in the final 18 months of their degree.…”
Section: Introductionmentioning
confidence: 99%